Performance and bromatologic analysis of red tail lambari Astyanax sp F (Pisces: characidae) submitted to the smoking process - Feiden, Aldi (2009)
The aim of this study was to evaluate the time of hot smoked and the influence of carcass quality of the red tail lambari Astyanax sp F. Sixty lambaris, eviscerated with head, skin, bones, spinal column, fins, however, without scale. With a medium weight and length of 22.22±4.32g and 11.32±00.63cm were utilized. The animals were submitted to humid salted (25% of sodium chloride for 45 minutes) and condiments, been later hot smoked for a period of 90, 180, 270, 360 min. After the smoking process, the fish were weighted and later the humidity tenor, gross protein, lipids and mineral matter of the carcass of the animals were calculated. The results showed differences  (P < 0.01) for performance, presenting the best use for the time of 90min followed by treatments of 180 and 270 min, but presented LRP (linear Response Plateau) for the time of 225:07 min, demonstrating that the intermediate treatments presented good performance. For the protein tenor, lipids and mineral matter, there were no differences (P < 0.05) between the different smoking time. Therefore, it can be concluded that the smoking time of 225min7seg for the Astyanax sp F, is the indicated smoking time for the best final product.